Splošni razlagalni slovarji slovanskih jezikov - Perdih, Andrej (Lingua Slovenica, 2016)
The monograph ('General Monolingual Dictionaries of the Slavic Languages') provides an overview of the more prominent dictionary typologies, and an overview of general monolingual Slavic language dictionaries created from 1945 untill the present. The analysis presents how dictionary elements of selected dictionaries are treated at the macrostructural and microstructural level. For selected elements (homonymy and homography, multi-word headwords, sub-entries, grammatical information, referential definition type, multi-word lexical units and etymological information), suggestions for further lexicographical practice are given. The standpoint of these suggestions is that a dictionary serves as a representation of a lexicon and as a practical tool, which should effectively and transparently deliver reliable and relevant linguistic data and to a lesser extent non-linguistic data. The suggestions also take into account the completed transition from the initial print dictionary to the initial electronic dictionary, which to a certain extent requires reallocation of the data and to a lesser extent reorganization of data hierarchy.